Initiations of Employer Engagement in Training Delivery of TVET Programmes - Shrestha, Rajendra Bahadur (Journal of Training and Development, 2021)
Engagement of employers in the Technical Vocational Education and Training (TVET) system is needed not only to increase the training capacity but to ensure the TVET is demand-driven, quality oriented, future focused and provides the economy with the skilled workers it needs. Employer engagement in TVET system covers a spectrum of cooperation and involves small participation to build the trust required to develop more robust long-term engagement strategies. Developing engagements with employer and employer’s associations at all levels of the training programmes life cycle facilitate the development of workable solutions for training-to-work transitions. The employer has a crucial role to play in the delivery of training programmes. Engagement of employer is an essential component of overall training programmes and leads to developing responsive labour market skill needs, supporting priority economic sectors, training design and development, training delivery and post training support to develop ongoing dialogue with employer and employer associations. The need to increase the engagement of employers in TVET programmes has been known for many years in the country, however, employer engagement in training delivery of TVET programme is under-explored in Nepal. This article addresses the existing situation, explores issues, and share some practicable initiations of employer engagement in the TVET programme.